Análise do perfil periodontal, socioeconômico, uso de tabaco e álcool em mulheres transgênero sob terapia hormonal - Mendes, José Wilson Silva [UNESP] (UNESP, 2025)
The study aimed to analyze the socioeconomic profile, tobacco and alcohol use, and periodontal conditions of transgender women undergoing hormone therapy. A total of 30 participants enrolled in the **Transforming Smiles (ICT/UNESP)** extension project were evaluated. Periodontal parameters — probing depth, clinical attachment level, gingival recession, and bleeding on probing — were collected, along with socioeconomic information based on the ABEP criteria and data on tobacco and alcohol consumption using the **Fagerström** and **AUDIT** questionnaires. Statistical analysis was performed using nonparametric tests (Mann-Whitney, Spearman, Kendall tau, and Kruskal-Wallis). The sample had a mean age of 33 years, a predominance of lower socioeconomic classes, a high frequency of alcohol consumption (86.7%) with low dependence risk, and smoking prevalence of 40%. Periodontal parameters indicated a condition compatible with mild periodontitis, with no statistically significant differences between smokers and non-smokers and no relevant correlations between socioeconomic status, alcohol/tobacco use, and periodontal outcomes. In conclusion, transgender women undergoing hormone therapy presented periodontal health compatible with moderate gingival inflammation, with no significant association with smoking, alcohol consumption, or socioeconomic profile, reinforcing the need for inclusive and integrated dental care approaches for this socially vulnerable population.

Objetivo: Analisar o perfil socioeconômico, o uso de tabaco e álcool, e as condições periodontais de mulheres transgênero em terapia hormonal. Materiais e métodos: Foram avaliadas 30 mulheres transgênero em acompanhamento no projeto de extensão Transformando Sorrisos (ICT/UNESP). Foram coletados parâmetros periodontais (profundidade de sondagem, nível de inserção clínica, recessão gengival e sangramento à sondagem), informações socioeconômicas pelo critério ABEP e dados sobre consumo de tabaco e álcool pelos questionários Fagerström e AUDIT. A análise estatística foi conduzida com testes não paramétricos (Mann-Whitney, Spearman, Kendall tau e KruskalWallis). Resultados: A amostra apresentou média de idade de 33 anos, predominância em classes socioeconômicas mais baixas e elevada frequência de consumo de álcool (86,7%), embora com baixo risco de dependência. O tabagismo esteve presente em 40% das participantes. Os parâmetros periodontais indicaram quadro compatível com periodontite leve. Não foram observadas diferenças estatisticamente significativas entre fumantes e não fumantes, nem correlações relevantes entre condição socioeconômica, uso de álcool/tabaco e desfechos periodontais. Conclusão: Mulheres transgênero em terapia hormonal apresentaram saúde periodontal compatível com inflamação gengival moderada, sem associação significativa com tabagismo, consumo de álcool ou perfil socioeconômico. Os resultados reforçam a necessidade de abordagens odontológicas inclusivas e integradas para essa população em situação de vulnerabilidade social.
Analysis of periodontal and socioeconomic profile, tobacco and alcohol use in transgender women under hormone therapy
Keywords: Mulheres transgênero; Terapia de reposição hormonal; Saúde Bucal; Doenças periodontais; Tabagismo; Transgender persons; Hormone replacement therapy; Oral health; Periodontal diseases; Tobacco use disorder